2001
DOI: 10.1021/jp0044680
|View full text |Cite
|
Sign up to set email alerts
|

Orientational and Vibrational Relaxation Dynamics of Perylene and 1-Methylperylene in Aldehydes and Ketones

Abstract: We report on the rotational diffusion and vibrational population relaxation dynamics of the probe molecules perylene and 1-methylperylene in selected aliphatic aldehyde and ketone solvents. The reorientation data demonstrate that, for both solvent systems, there is a change in the nature of the solvent−solute interactions with both probe molecules as the hydrodynamic volume of the solvent molecules approaches that of the probes. The solvent-dependent change in behavior occurs for different solvent aliphatic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 60 publications
4
26
1
Order By: Relevance
“…Therefore, τ 3 can be assigned to VET or SA-IVR. Blanchard et al reported an analysis of VER of ground-state (S 0 ) perylene in several ketone solvents by using picosecond stimulated emission spectroscopy, and found that the VET rates were in 10 -50 ps range [9]. This time constant is much longer than the τ 3 value observed in the present study, 1.8 -4.9 ps, even taking the difference in the electronic states, S 0 and S 1 , into account.…”
Section: Resultscontrasting
confidence: 52%
See 4 more Smart Citations
“…Therefore, τ 3 can be assigned to VET or SA-IVR. Blanchard et al reported an analysis of VER of ground-state (S 0 ) perylene in several ketone solvents by using picosecond stimulated emission spectroscopy, and found that the VET rates were in 10 -50 ps range [9]. This time constant is much longer than the τ 3 value observed in the present study, 1.8 -4.9 ps, even taking the difference in the electronic states, S 0 and S 1 , into account.…”
Section: Resultscontrasting
confidence: 52%
“…This sudden drop-off of decay rates, which is common for τ 2 and τ 3 processes, may be attributed to the change in structure of solvation cavity surrounding perylene. Goldie and Blanchard measured reorientation dynamics of perylene in ketone solvents, and reported that the reorientation of perylene can be expressed by a single exponential decay function for the C 5 -C 8 ketone solvents while by a double exponential decay for the C 9 ketone solvent [9]. These results indicate that the structure of solvation cavity surrounding perylene changes from prolate for the C 5 -C 8 ketones to oblate for the C 9 ketone [9,26].…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations